After the Reich the brutal history of the Allied occupation - MacDonogh, Giles 1955- (Basic Books, 2007)
In After the Reich, Giles MacDonogh has written a comprehensive history of Germany and Austria in the postwar period, drawing on a vast array of contemporary first-person accounts of the period. In doing so, he has finally given a voice the millions of who, lucky to survive the war, found themselves struggling to survive a hellish "peace."